Prevalence of canine leptospirosis in Tiruchirappalli, Tamil Nadu - Lakshmipriya, C; Anandhagiri, S; Nataerajaseenivasan, K (The Indian Journal of Animal Sciences, 2012)
Canine leptospirosis is prevalent worldwide and generally associated with infection by Leptospira interrogans serovar Canicola and Icterohaemorrhagiae. Present study was aimed to determine the incidence and prevalence of canine leptospirosis and also to determine the utility of the 16S rRNA sequence based diagnosis of canine leptospirosis in comparison with the standard microscopic agglutination test (MAT). In total 135 blood samples were collected consisting of both domestic and stray dogs attending the veterinary polyclinic for the treatment of febrile illness. The leptospiral infection was determined by MAT, ELISA and nested PCR analysis. The present investigation showed an overall seroprevalence of 37.7% (51/135) with the predominant serovar to be Autumnalis 9.6% (13/135), followed by Icterohaemorrhagiae 8.14% (11/135), Canicola 8.14% (11/135) and Javanica 6.66% (9/135). Thus the surveillance of canine leptospirosis is an important tool for detecting the risk of exposure in human and it provide an insight about the important prevailing circulating serovars. In the present study 16S rRNA nested PCR for the diagnosis of canine leptospirosis showed a sensitivity 92%, specificity 73%, PPV 68%, NPV 93%, respectively on comparison with MAT which envisaged the detection of canine leptospirosis at the acute phase of the disease.